Self-assembled ZnO-carbon dots anode materials for high performance nickel-zinc alkaline batteries - Wei, Ji-Shi; Zhu, Ze-Yang; Zhao, Xiao; Song, Tian-Bing; Huang, Jian-Hang; Zhang, Yi-Xiao; Liu, Xi; Chen, Liwei; Niu, Xiao-Qing; Wang, Yong-Gang; Xiong, Huan-Ming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
After incorporation of a few Carbon Dots (CDs), ZnO anodes process thin carbon shells, refined microstructures and special univalent zinc sites, which result in better reactivity, higher corrosion resistance, more effective electron paths to enhance electrochemical performance in high capacity, excellent rate capability and long cycling stability in the Ni-Zn alkaline battery. [Display omitted] •1. CDs efficiently control morphology of ZnO for sufficient electrochemical reactions.•2. With the assistance of CDs, ZnO will process conformal carbon shells with few layers.•3. Univalent zinc sites constructed by CDs play a key role during charging process. The development of high-performance nickel-zinc (Ni-Zn) alkaline batteries is mainly plagued by short life span and poor rate performance of ZnO anode materials. To improve the cycling stability and rate capability of Ni-Zn batteries, carbon dots (CDs) are employed to construct clustered ZnO-CDs nanocomposites, coating ZnO with protective shells of carbon layers and providing electron paths to enhance conductivity of the nanocomposites. Univalent zinc species are found at the interfaces between CDs derivatives and ZnO, which are embedded in the nanoclusters and protected well by carbon coating. Theoretical calculations show univalent zinc species change the electronic structures of ZnO surface, so as to accelerate the charging process of ZnO anode materials. Such ZnO-CDs derived nanocomposites exhibit excellent rate capability (95.3%, 84.7% and 75.0% of capacity retention rate at 2, 5 and 10 A g−1, respectively) and outstanding cycling stability with 92.0% of capacity retention rate after 5000 cycles, which is far better than ZnO based anodes without the protection of CDs (39.1% retention rate from 1 to 10 A g−1 and 71.6% of capacity retention rate after 500 cycles).